(untitled) (International Journal of Physiology, 2019)
Background Despite of extensive management programmes for iron deficiency anaemia, it remains a challenge for healthcare professionals. So, there is a requirement of supplementing the conventional therapy with some micronutrients which have a possible role in combating the problems of anaemia. Vitamin A is one of those possible micronutrients. Material and Method Adolescent girl students from a school who were diagnosed as anaemia were categorised randomly into two interventional groups. Those who were not diagnosed as anaemia formed the third group. In group A, Vitamin A supplementation (2, 00, 000 IU single dose) along with Iron in the form of FeSO4 was given for 100 days. Group B students received only Iron supplementation for the same period. Only placebo was given to the students of group C. Results In group A the mean value for blood haemoglobin improved from 10.128+0.196 gm/dL to 12.216+0.215 gm/dL. The improvement was extremely significant (p<0.0001). In group B mean value for blood haemoglobin improved from 10.141+0.210 gm/dL to 11.766+0.218 gm/dL and was very significant (p<0.0001). In group C, the mean value for blood haemoglobin was 12.809+0.099, which significantly improved to 13.018+0.119 gm/dL. (p=0.008). The %age change over baseline was more in group A (20.39%) than group B (12.38%) as compared to group C (2.77%). Conclusion This study concluded that vitamin A supplementation helps to restore the blood haemoglobin level along with iron therapy and helps to improve the status of anaemia. Further studies involving large population are required to establish the definitive role of vitamin A supplementation in anaemia and to recommend it as a standard additive therapeutic agent.